Unusual Complication of Hemodialysis Cuffed Catheter Tunnel Infection and Unconventional Therapeutical Decision: A Report of Two Cases - Biser K. Borisov; Stela P. Linkova (Case Reports in Surgery)
Introduction. Infectious complications are the most common chronic complications observed in patients undergoing hemodialysis with central venous catheters. However, despite the efforts of a large number of medical professionals, tunnel catheters are increasingly being used for hemodialysis in the everyday practice. Case Report. We describe two cases of an equal complication of a tunnel infection wherein the catheter becomes naked after self-rupture of the purulent secretion. We did not replace the tunnel catheter but applied a skin plastic by rotation flaps over the affected area, which proved to be sufficient. Six months after the intervention, the patients continue their hemodialysis treatment using the same cuffed catheters; the taken chemocultures do not give rise only to bacterial growth and skin plastic has been healed primary. Conclusions. The two cases described by us represent one treatment option, which may be discussed with reference to such specific two cases in practice.